Pengembangan Aplikasi Android Rekomendasi Tempat Gym di Kota Malang yang menerapkan Protokol Kesehatan Covid-19 - Asrina Fitri; Ratih Kartika Dewi; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
In December 2019, there was a phenomenon that made people all over the world restless, namely the corona virus outbreak (Covid-19). The Indonesian government has made various efforts to prevent the spread of this virus. In the process of implementing it, there are many pro and con responses from the community, one of which is doing sports in the gym. This is due to the closed condition of the room and the number of people in the room (Setyaningrum and Yanuarita, 2020). This study aims to help restore people's confidence to do sports in the gym again by creating a recommendation application system as desired by the user, so that users can apply the important points of PHBS, namely exercising. This recommendation application system adopts the Location Based Service (LBS) concept by utilizing the Google Maps API and the SAW calculation method, the community can make decisions about gym places that have implemented the Covid-19 health protocol in Malang City. The results of testing the system from the recommendation application for a gym in Malang City that applies the Covid-19 health protocol using 3 types of tests, namely Black-box testing with 100% valid functional test validation results, algorithm validation testing with 100% valid results, and usability testing to application users with the SUS approach get 83.5 results, namely grade B (good) at grade scale, then acceptable at acceptability, and excellent at adjective rating (Ependi, et al., 2017).